EFFECT OF THE FLAVONOID 6-AMINOFLAVONE IN ASPIRIN-INDUCED GASTRIC ULCER IN SPRAGUE-DAWELY RATS: A HISTOMORPHOLOGICAL STUDY - Tahira Mehreen; Aamir, Shabnum; Nadeem Ali Shah; Muhammad Shahid; Irum Javaid; Munayal Roghani; Arslan Roghani; Faizan Roghani (Journal of Ayub Medical College Abbottabad, 2022)
Background: The analgesic drugs are the main cause of gastric ulcer. The objective of this study was to determine the gastroprotective ability of flavonoid, 6-aminoflavone in a rat pyloric ligation model of aspirin associated gastro-ulcerogenesis. Methods: A laboratory based experimental study was conducted in the animal house and research laboratory at Khyber Medical College, Peshawar from July to November 2019. A total of 42 adult male Spargue-Dawely rats were divided into seven groups. Flavonoid, 6-aminoflavone was administered orally in doses of 10, 25 and 100 mg/kg with misoprostol, as standard at 50 µg/kg orally for 4 days. On the last day aspirin was given orally at 200 mg/kg and the pyloric ligation surgery was performed. After 4 hours all animals were killed by cervical dislocation. The gastric tissues were collected for histomorphological study. The obtained data were expressed as mean±SEM. Analysis was carried out by using ANOVA. p value Ë‚0.05 was considered significant. Results: The animals treated with the different doses of 6-aminoflavone showed a marked protective effect in the histological observations. The 10 mg/kg dose had a mild protective effect as occasional ulcerative changes were observed. However, doses of 25 and 100 mg/kg significantly caused the reduction in the ulcer score. These effects produced were equipotent to the gastroprotective effectiveness inherent in the misoprostol. Conclusion: These findings conclude that 6-aminoflavone as like other flavonoids has a significant gastroprotective propensity with significant effect produced at doses of 25 and 100 mg/kg and can be used as a part of therapy management for the treatment of gastrointestinal disease particularly ulcerative condition.